Highly Flexible Freestanding BaTiO3‐CoFe2O4 Heteroepitaxial Nanostructure Self‐Assembled with Room‐Temperature Multiferroicity. Issue 3 (23rd November 2021) - Zhong, Gaokuo; An, Feng; Qu, Ke; Dong, Yongqi; Yang, Zhenzhong; Dai, Liyufen; Xie, Shuhong; Huang, Rong; Luo, Zhenlin; Li, Jiangyu
Abstract: Multiferroics with simultaneous electric and magnetic orderings are highly desirable for sensing, actuation, data storage, and bio‐inspired systems, yet developing flexible materials with robust multiferroic properties at room temperature is a long‐term challenge. Utilizing water‐soluble Sr3 Al2 O6 as a sacrificial layer, the authors have successfully self‐assembled a freestanding BaTiO3 ‐CoFe2 O4 heteroepitaxial nanostructure via pulse laser deposition, and confirmed its epitaxial growth in both out‐of‐plane and in‐plane directions, with highly ordered CoFe2 O4 nanopillars embedded in a single crystalline BaTiO3 matrix free of substrate constraint. The freestanding nanostructure enjoys super flexibility and mechanical integrity, not only capable of spontaneously curving into a roll, but can also be bent with a radius as small as 4.23 µm. Moreover, piezoelectricity and ferromagnetism are demonstrated at both microscopic and macroscopic scales, confirming its robust multiferroicity at room temperature. This work establishes an effective route for flexible multiferroic materials, which have the potential for various practical applications. Abstract : High quality heteroepitaxial freestanding 1D–3D type multiferroics of self‐assembled BaTiO3 ‐CoFe2 O4 (BTO‐CFO) nanostructure with CFO pillars embedded in BTO matrix is prepared based on a water‐dissolvable Sr3 Al2 O6 sacrificial layer. The freestanding BTO‐CFO nanostructure enjoys super flexibility and mechanical integrity, and clear piezoelectric and magnetic responses confirming its robust multiferroic properties at room temperature.